PERMAINAN MONOPOLI RELIGIUS DALAM MENINGKATKAN PERILAKU RELIGIUS ANAK USIA 4-5 TAHUN - Yuli Tri Andini; Siti Markamah (AL IHSAN: Jurnal Pendidikan Islam Anak Usia Dini, 2021)
Behavior religious is thing that need in embed since early years because it will give impact in the future in adult. However on reality still lots found behavior child that not show their religious behavior as recite prayer, daily behavior prayer and etc. This research aim for knowing influence game monopoly religious to behavior religious child in age 4-5 year in RA Al-Futuyyah. As for method that used descriptive qualitative with technique collection data observation and interview. Result that child age 4-5 years in RA Al Futuyyah Muncar have behavior religious that develop correspondeing after given game monopoly religious. Thing this from 20 child there is 15 child got result develop corresponding hope while 5 other got result want develop.